The Reasonable (Munasabah) of the Qur'an in Learning the Interpretation of the Qur'an - Wahid, Fadhilah Nur (UIN Sunan Gunung Djati Bandung, 2025)
The relevance of munāsabah—the study of thematic and structural coherence between Qur’anic verses and chapters—has long been a subject of scholarly debate. While some classical exegetes regard it as a foundational approach in unlocking the Ilahi unity of the Qur’an, others question its significance due to the diverse contexts of revelation. This study aims to explore the theoretical foundations of munāsabah and examine its pedagogical relevance in contemporary Qur’anic exegesis. Employing a qualitative library research method and a descriptive-analytical approach, this study critically engages with classical works, particularly Mafātīḥ al-Ghayb by Fakhruddin al-Rāzī and Naẓm al-Durar by Al-Biqāʿī. The findings reveal that munāsabah plays a pivotal role in demonstrating the Qur’an’s thematic coherence, deepening spiritual insight, and enhancing the methodological rigor of tafsir education. It is concluded that munāsabah is not merely a stylistic or rhetorical device but a vital exegetical framework that enriches both the cognitive and affective dimensions of learning the Qur’an. This research contributes to contemporary Qur’anic studies by reaffirming munāsabah as an integrative and indispensable interpretive tool in the teaching and understanding of the Qur’an.